Heavy metal induced histopathological alterations in liver of Channa gachua (Ham) - Deore, S V; Wagh, S B (Journal of Experimental Sciences, 2012)
Discharge of heavy metals into aquatic environment from various sources even below permissible levels, creates health hazards in aquatic organisms. The persistence and ubiquitous nature of these pollutant compounds coupled with their tendency to accumulate in organisms ultimately produce toxic reaction in aquatic biota especially, fish. This study aims to investigate histopathological impact of lethal (1.0625 ppm, 1.4202ppm) and sublethal (0.1062ppm, 0.0531ppm and 0.1420ppm, 0.0710ppm) concentrations of mercury chloride and copper chloride in liver of fresh water teleost, Channa gachua (Ham) .The histopathology studies revealed vacuolation in cytoplasm, degeneration of nuclei, vacuolation in stroma, cloudy swellings, pycnotic nuclei, necrosis, rupture of blood sinusoids, disarray of hepatic cords, loss of shape of hepatocytes. Severity of damage was found to be dose dependent and time of exposure.